Pengaruh Sosialisasi, Pendapatan, Dan Persepsi Risiko Terhadap Minat Berinvestasi Di Pasar Modal Syariah Pada Generasi Z Di Kota Langsa - Mastura, Mastura; Silfi, Silfiya Nurzakia; Rifyal, Rifyal Dahlawy Chalil; yahya, M.Yahya (FEBI IAIN Langsa, 2024)
This study aims to analyze the influence of socialization, income, and risk perception on investment interest in the sharia capital market on generation z in Langsa City. This study is a type of quantitative research using primary data. The population in this study was 66,149 and the sample used was 100 respondents using a sampling technique based on purposive sampling and a data collection method using a questionnaire. The testing carried out in this study used the help of the SPSS 21 application with the multiple linear regression analysis method. The results of this study indicate that partially the variables of socialization and income have a significant effect on investment interest in the sharia capital market, while the variable of risk perception partially does not have a significant effect on investment interest in the sharia capital market. Simultaneously, all variables have a significant effect on investment interest in the sharia capital market.